There is an arithmetic progression whose first term is 36, and the sum of the first
n
terms of the AP is a perfect square for all positive integers
n
.
What is the 100th term of this arithmetic progression?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What if after 36, we added 13, 15, 17, 19..., which would yield sums of 49, 64, 81, 100...? Wouldn't this series also met all the terms and conditions. Pun intended.
Log in to reply
Is it an ap?
Log in to reply
Sorry, my mistake. I didn't realise it.
Log in to reply
@Nanayaranaraknas Vahdam – Sometimes it happens...
Ugg, dude, that's what I did. :O
U cannot add diff nos in an A.P..... In A.P, the difference b/w any 2 consecutive nos is always constant...... But in ur series, the difference is an A.P is not constant.........
Please explain what is p|S
Cool problem!
Why should we have (2a-d)=0....
Log in to reply
We have proved that every even prime divided 2a-d which is only possible if it is infinite but actually it is a finite quantity so it must be 0.
But 9 9 7 1 6 4 − 3 6 = 7 2 , which would be the number we add on to the sum S n to get S n + 1 , and 3 6 + 7 2 = 1 0 8 , which is not a perfect square.
Also, why can't 3 6 be an answer to this? If we start with S 1 = 3 6 (as in the problem), and add 0 to every term after, then the conditions stated in the problem would be satisfied, as the sum would always be 3 6 , which is a perfect square.
Log in to reply
I recommend reading the question carefully once again....I said the sum of the 1 s t n terms should be a perfect square not all the terms individually
1 . Following my method we get the series 3 6 , 1 0 8 , 1 8 0 , . . . .
Hence S 1 = 3 6 = 6 2 S 2 = 3 6 + 1 0 8 = 1 4 4 = 1 2 2 S 3 = 3 6 + 1 0 8 + 1 8 0 = 1 8 2
2 . Following your method we get the series 3 6 , 3 6 , 3 6 , . . . . .
Hence S 1 = 3 6 S 2 = 3 6 + 3 6 = 7 2 = ( 6 2 ) 2 S 3 = 1 0 8 = ( 6 3 ) 2 . None of which are perfect squares...
Firstly maybe you misunderstood the question and secondly your counter example is not true............
Log in to reply
Oh yes, I didn't read the question carefully. Woops
Your solution is very nice but I have doubt in one step, How did you conjecture that p divides Sp i.e p ∣ s p
That's the best solution I've seen so far.I too did it that way.Good problem with a nice solution.Upvoted&liked!!
A relatively well-known fact about the AP of a sequence of odd numbers is that the sum is always a perfect sqaure: 1, 1+3 = 4, 1+3+5=9 etc then we will just have to match the first term of this to the one of the question by multiplying each term by 36
Since 36 is a perfect square this property is preserved: for a n = 2 n − 1 where n ∈ Z : k = 1 ∑ n a k = n 2 then 3 6 k = 1 ∑ n a k = 3 6 n 2 = 6 2 n 2 = ( 6 n ) 2 which is still a perfect square
So now it reduces to finding the 100th term of this new sequence: a 1 0 0 ′ = 3 6 a 1 0 0 = 3 6 ( 2 × 1 0 0 − 1 ) = 7 1 6 4 The proof of sum of odd numbers equal to a perfect square can be trivially proven by induction or graphically and hence is omitted here.
I did it this way:
S(n) = 2 n [2a+(n-1)d] = m 2 ,where m is some positive integer.
Rearranging terms in L.H.S,
( 2 d ) n 2 + (a- 2 d ) n = m 2
The only way to complete the square on the L.H.S is by making d=2a=72,
and so the sum of first n terms will be of the form S(n)= m 2 = ( 6 n ) 2 .
Hence the 100th term will be a+(100-1)d= 7 1 6 4 .
But you should have proven that d=72.Otherwise u can not claim that it's the only possible value for d.
This is my solution (Sorry, I don't know how to use LaTeX here): The terms of this AP are 36, 36+a, 36+2·a, ... So the sum of the first n terms is: S n = 36 + (36+a) + (36+2·a) + ... + (36 + (n-1)·a) = (36 + ... + 36) + (0·a + 1·a + 2·a + ... + (n-1)·a) Therefore, S n = 36·n + a·n·(n-1)/2 If we expand that expression, we have S n = 36·n - (a/2)·n + (a/2)·n^2 = (36 - a/2)·n + (a/2)·n^2 So one realizes that it would be enough if a/2 were 36, since S n would be a perfect square: S_n = 36·n^2. Hence, we are looking for a = 72. With that, the 100th term of the AP is 36 + 99·72 = 7164
Let d be the common difference of the AP. We want that ∑ i = 1 k a k = s q u a r e , for any k ∈ { 1 , 2 , . . . , 1 0 0 } .Is simple to see that the sum is 3 6 k + d 2 k ( k + 1 ) , and so we want
3 6 k + d 2 k ( k + 1 ) = s q u a r e for any k .
Rearranged the sum like 3 6 ( k + d 7 2 k ( k + 1 ) )
and see that if d = 7 2 we have
∑ i = 1 k a k = 3 6 k 2 for any k.
So d = 7 2 and a 1 0 0 = 3 6 + 9 9 × 7 2 = 1 7 6 4
First of all, nothing in the problem description says the constant sequence a n = 3 6 $ cannot be a solution. Secondly, the solution is best done by drawing. Draw a 1x1 square. To get a 2x2 square, you add 3. To get a 3x3 square you add 5. Conclusion: the sum of the first n odd numbers is a perfect square. So let a n = 2 n − 1 . However, we want our sequence to start with 36, with is a perfect square, so we multiply a n with 36 to get b n = 7 2 n − 3 6 . This is our sequence. It works, because the product of a square and a square is a square.
Can you please clarify how the constant sequence can be a solution???I said that the sum of the n terms should be a perfect square not each term individually.....To learn why the constant sequence cannot be an answer read my reply to Milly ChooChoo...........
Problem Loading...
Note Loading...
Set Loading...
Solution. We will prove it in a more general case,let us take the 1 st term to be k 2
When n = 1 ,the sum of the first term is a perfect square = k 2 .
The sum upto the n -th term is S n = 2 n [ 2 a + ( n − 1 ) d ] ,since these are all perfect squares we have [ 2 a + ( n − 1 ) d ] > 0 and hence d > 0
Now let us choose any odd prime p . S p = 2 p [ 2 a + ( p − 1 ) d ]
Since p ∣ S p and S p is a perfect square, p 2 ∣ S p , p ∣ ( 2 a − d ) + p d p ∣ ( 2 a − d ) This relation is true for all primes p ,but since ( 2 a − d ) is finite,we must have 2 a − d = 0 and hence d = 2 a = 2 k 2
So the series is k 2 , 3 k 2 , 5 k 2 , . . . . . . . .
In other words,the n -th term is t n = ( 2 n − 1 ) ∗ k 2 .
In this problem clearly k = 6 ,So the 1 0 0 -th term of the series will be = ( 2 ∗ 1 0 0 − 1 ) ∗ 6 2 = 7 1 6 4